Targeting New Pathways and Cell Death in Breast Cancer - Aft, Rebecca L. (IntechOpen, 2012)
This book presents novel in interesting find by multiple accomplished investigators in breast cancer. These chapters elucidate new mechanisms of breast cancer cell death as well as discuss new pathways for therapeutic targeting.